Study about profile and distribution of padel courts n the Autonomous Community of Extremadura - Diego Muñoz Marín; Bernardino Javier Sánchez-Alcaraz Martínez; Javier Courel-Ibáñez; Eduardo Romero Pastelero; Francisco Javier Grijota Pérez; Jesús Díaz Garcia (E-balonmano.com: Revista de Ciencias del Deporte, 2016)
The aim of this study was to assess padel facilities and its characteristics in the Autonomous Community of Extremadura according to the number of inhabitants. The totality of the padel courts built in this area was registered considering property, structure, the pavement surface and the location. The results show a total of 649 padel courts in Extremadura (409 in province of Badajoz and 240 in province of Cáceres). Public facilities account for the 50% of the total, however we found large differences between the provinces (44,25% in Badajoz and 57,92% in Cáceres). Likewise, similar density were observed between provinces but not when comparing districts. Regarding court profile, 93,05% had an artificial turf ground, 68,26% had a glass enclosure and 69,34 had an outdoor location.